Does the Community of Inquiry Framework Predict Outcomes in Online MBA Courses? - Arbaugh, J. B. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
While Garrison and colleagues’ (2000) Community of Inquiry (CoI) framework has generated substantial interest among online learning researchers, it has yet to be subjected to extensive quantitative verification or tested for external validity. Using a sample of students from 55 online MBA courses, the findings of this study suggest strong empirical support for the framework and its ability to predict both perceived learning and delivery medium satisfaction in online management education. The paper concludes with a discussion of potential implications for online management education researchers and those interested in further study of the CoI framework.